Deep History, Secular Theory Historical and Scientific Studies of Religion. - Martin, Luther (Boston : De Gruyter, 2014)
Over the course of his career, Luther H. Martin has experimented with methodological approaches to the study of religion, particularly Hellenistic religions. This volume represents Martin's shift from comparative to socio-political to scientific studies of religion, and especially to the cognitive science of religion. The 25 contributions collected here, selected from over 100 essays, are representative of his work over the past two decades.
19. Performativity, Narrative, and Cognition: "Demythologizing" the Roman Cult of Mithras20. Cognitive Science, Ritual, and the Hellenistic Mystery Religions; 21. Why Christianity Was Accepted by Romans but Not by Rome; 22. Aspects of Religious Experience among the Hellenistic Mystery Religions; 23. The Uses (and Abuse) of the Cognitive Sciences for the Study of Religion; 24. The Future of the Past: The History of Religions and Cognitive Historiography; Author Index; Subject Index.
Print version record.
Keywords: Religion -- History; Religion; Theology; Religion; Religions; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books